Greenland, Northeast entrance to Mackenzie Bay, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Aug 18, 1931. East coast of Greenland, Hold with Hope - Hudson's Land, Cape Broer Ruys and Northeast entrance to Mackenzie Bay.